2019
DOI: 10.1007/s00894-019-3999-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of fentanyl bound to μ-opioid receptor

Abstract: The molecular dynamics simulations of fentanyl complexed with the μ-opioid receptor (μOR) were studied using both inactive 4DKL and active 5C1M opioid receptor crystal structures. Analogous simulations in morphine with or without a ligand were done for comparison. Simulations of the inactive states were carried out in the absence and presence of the Na + ion. The obtained fentanyl's binding mode agrees with some of the mutagenesis data, and it overlaps with that of morphine only to a minor extent. Notably, fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(110 citation statements)
references
References 53 publications
9
101
0
Order By: Relevance
“…Morphine was also shown to form stable hydrophobic interactions with His297 (protonation state unclear) in a recent MD study. 17 The de novo binding simulations of the Filizola group showed that oliceridine (TRV-130) which has an atypical chemical scaffold binds mOR via water-mediated interactions between the charged amine group and Asp147, while frequently contacting His297 (protonation state unclear). 32 While consistent with these studies, our data uncovered an unexpected role of the tautomer state in modulating the fentanyl-binding mechanism.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphine was also shown to form stable hydrophobic interactions with His297 (protonation state unclear) in a recent MD study. 17 The de novo binding simulations of the Filizola group showed that oliceridine (TRV-130) which has an atypical chemical scaffold binds mOR via water-mediated interactions between the charged amine group and Asp147, while frequently contacting His297 (protonation state unclear). 32 While consistent with these studies, our data uncovered an unexpected role of the tautomer state in modulating the fentanyl-binding mechanism.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Considering the lack of sodium presence in the active mOR, two previous MD studies used a protonated Asp114, 8,10 while published work did not specify the protonation state. 17,31,32 Recently, the pK a of D 2.50 in M2 muscarinic acetylcholine receptor (m2R) was calculated using the Poisson-Boltzmann method with a protein electric constant of 4. 35 The calculation gave a pK a of 8-12 when sodium is 5 Å away from D 2.50 .…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Phe3 in 1 and Phe4 in DAMGO are situated in the same S2 site. S2 is also occupied by phenyl rings of small molecular agonist BU72 in 5 C1 M [12] crystal structure ( Figure S18) or of fentanyl [32,33] according to molecular modeling ( Figure S19). The analogues of 1 were predicted to bind in orientations largely similar to that of the parent compound.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The receptor was placed in a phosphatidylcholine (POPC) membrane and solvated with the TIP3P water model; the CHARMM36 force-field was used. The simulation runtime was 1.2 s [71].…”
Section: Using Molecular Dynamics Simulations To Study Gpcr-ligand Bimentioning
confidence: 99%